Incidence of neurological complications of surgery for congenital heart disease. Issue 5 (May 1995) - Fallon, P; Aparício, J M; Elliott, M J; Kirkham, F J
Abstract : A total of 523 cardiac surgical discharge summaries were searched for recorded evidence of adverse neurological events occurring between operation and time of discharge. Neurological events were recorded in 31 and included one or more of seizure disorder (n = 16), pyramidal signs (n = 11), extrapyramidal signs (n = 8), coma (n = 6), and neuro-ophthalmic deficits (n = 6). There were significantly more adverse neurological events after repairs for arch anomalies (16.6% of cases). There was also an association with the length of cardiopulmonary bypass and a period of low perfusion pressure either intraoperatively or postoperatively. Of the 19 out of 23 survivors in whom long term outcome data were available, four were normal and six had persisting neurological problems directly related to the perioperative period. In a further nine of the 19 survivors, established preoperative neurodevelopmental abnormality probably contributed to their present neurological status, in addition to perioperative events. In view of the way these data were collected, this study must represent the minimum incidence of neurological events in children undergoing cardiac surgery.